Investigating the Role of Artemin and Its Cognate Receptor, GFRα3, in Osteoarthritis Pain - Minnema, Laura; Gupta, Ankita; Mishra, Santosh K.; Lascelles, B. Duncan X. (Frontiers in Neuroscience, 2022)
Osteoarthritis (OA) associated pain (OA-pain) is a significant global problem. OA-pain limits limb use and mobility and is associated with widespread sensitivity. Therapeutic options are limited, and the available options are often associated with adverse effects. The lack of therapeutic options is partly due to a lack of understanding of clinically relevant underlying neural mechanisms of OA-pain. In previous work in naturally occurring OA-pain in dogs, we identified potential signaling molecules (artemin/GFRα3) that were upregulated. Here, we use multiple approaches, including cellular, mouse genetic, immunological suppression in a mouse model of OA, and clinically relevant measures of sensitivity and limb use to explore the functional role of artemin/GFR3 signaling in OA-pain. We found the monoiodoacetate (MIA)-induced OA-pain in mice is associated with decreased limb use and hypersensitivity. Exogenous artemin induces mechanical, heat, and cold hypersensitivity, and systemic intraperitoneal anti-artemin monoclonal antibody administration reverses this hypersensitivity and restores limb use in mice with MIA-induced OA-pain. An artemin receptor GFRα3 expression is increased in sensory neurons in the MIA model. Our results provide a molecular basis of arthritis pain linked with artemin/GFR3 signaling and indicate that further work is warranted to investigate the neuronal plasticity and the pathways that drive pain in OA.